Experimental and numerical study performed on seismic behavior of irregular external SRC joints in the main plant of CAP1400 NPP. (15th August 2020) - Liu, Biao; Bai, Guo-Liang; Zhao, Jin-Quan; Li, Jia-Rui
Highlights: Quasi-static cyclic testing of irregular external SRC joints in the main plant of CAP1400 NPP; Detailed 3D finite element model; Modelling technique for considering bond-slip behavior; Parametric study performed on irregular external SRC joints; "Measurement" of effective and economical reinforcement. Abstract: The main plant of steel reinforced concrete (SRC) structure is proposed for CAP1400 nuclear power plant (NPP) in high seismic zone, which not only has better mechanical properties than reinforced concrete structure plant, but also has lower maintenance cost than steel structure plant. The irregular SRC joints are inevitably appeared in the main plant due to the limitations of power generation technology and equipment. In this paper, quasi-static cyclic tests were carried out on three 1:4 reduced scale irregular external SRC joints to discuss the seismic performance of the joints in the NPP, mainly including the damage pattern, hysteretic behavior, load carrying capacity, stiffness degradation and ductility. In addition, the detailed 3D finite element (FE) models were established, in which the bond-slip behavior between the shaped steel and concrete was considered by using the developed software to add a huge number of non-linear spring elements, and the FE models were verified by the test results. Then, the parametric study on seismic performance of irregular external SRC joint was carried out, and the influence of each parameter on the seismic performance of the irregular external SRC joint was analyzed. Finally, the effective and economical reinforcement measures were proposed, and verified by the FE method.